√(2-3x) = 9
2-3x = 81
3x = -79
x = -79/3
Remember: (a-bx)^2 is NOT NOT a^2 - b^2x^2
Not that that matters here, anyway, since
√(stuff)^2 is just stuff, whatever stuff you have.
(√x)^2 = √(x^2) = x. There is no reason at all to square what's inside the radical. It just emerges unchanged when the square toot is squared.
Find all solutions to the equation sqrt(2-3x)= 9. Express your answer as a common fraction.
I squared both sides and I got 4-9z^2=81 and then -9z^2=77 then I divided both sides by -9 and now I am stuck, I know I can square root both sides. But I think something went wrong.
1 answer